Enterprises and Workers in the Transition: Econometric Evidence - Švejnar, Jan (American Economic Review, 1996)
The Central and East European (CEE) countries are in their sixth year of a dramatic transition from a centrally planned to a market-based system. In the first phase of the transition, most of these economies have achieved macroeconomic stabilization but also experienced a major decline in officially measured output and a slower but significant decline in employment. The attention has thus shifted to the ability of governments to check the rapid rise in unemployment, induce efficient behavior of firms, and improve the functioning of the infant markets. In particular, while a fundamental feature of the centrally planned economies was full employment, with state enterprises hoarding unproductive labor, a distinguishing feature of the transition has been the emergence of a double-digit unemployment rate, together with varying degrees of restructuring, privatization, and birth of firms. An understanding of these phenomena is essential for grasping the process of transition and formulating appropriate policies. In this paper, I provide a step in this direction by discussing some recent econometric evidence for CEE on (i) enterprise behavior (in the areas of restructuring and privatization, as well as employment and wage setting) and (ii) the flow of individuals from unemployment into employment.